Fear and stress related to COVID-19 and associated factors among undergraduate nursing students in Qatar - Vahe Kehyayan (8962580) (2023)
Background The emergence of the coronavirus disease (COVID-19) has had an impact on nearly every human being with millions of related infections and deaths. The negative impact of the pandemic on individuals' mental health such as fear and stress, particularly among university students, have been reported. While the switch to online teaching and learning played an important mitigating role, it also had presented additional challenges to students' mental health. Aim To examine the prevalence of fear and stress among undergraduate nursing students in Qatar and the factors associated with fear of COVID-19. Method A cross-sectional design. An online survey was sent to students at the University of Calgary in Qatar. Results 135 participants completed the survey. The findings showed differences in fear of COVID-19 and stress and satisfaction with the measures proposed by the academic institution based on participants' demographic and COVID-19 profiles. Furthermore, fear of COVID-19 was associated with the age group (26–35), academic year level, and satisfaction with the measures proposed by the academic institution. Conclusion The study found that switching teaching and learning online had a negative impact on participants' fear and stress. Several strategies were suggested to alleviate students' fear and stress and support them during future pandemics. Other Information Published in: Applied Nursing Research License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.apnr.2023.151727